Should the side-hop test be reduced from 40 cm to 30 cm when used in developmental athletes? - Schneider, I.; Kammann, N.; Haertel, O. (British Journal of Sports Medicine, 2021)
Background The side-hop test by Gustavsson et al. (2006) helps with return to play decision making after lower extremity injury.